Blood flow restriction augments exercise-induced pressure pain thresholds over repetition and effort matched conditions - Hammert, W. B.; Song, J. S.; Yamada, Y.; Kataoka, R.; Wong, V.; Spitz, R. W.; Seffrin, A.; Kang, A.; Loenneke, J. P. (Journal of Sports Sciences, 2024)
We sought to determine the effects of blood flow restriction (BFR) on exercise-induced hypoalgesia, specifically using low-load (LL) resistance exercise (30% 1RM) protocols that accounted for each individual`s local muscular endurance capabilities. Forty-four participants completed four conditions: (1) 70% of maximal BFR repetitions with blood flow restriction (LL+BFR exercise); (2) 70% maximal BFR repetitions without LL+BFR (LL exercise); (3) 70% maximal free flow repetitions (LL+EFFORT exercise); (4) time-matched, non-exercise control (CON). Pressure pain threshold (PPT) was measured before and after exercise. Ischaemic pain threshold and tolerance was assessed only at post. The change in upper body PPT was greater for LL+BFR exercise compared to LL exercise [difference of 0.15 (0.35) kg/cm2], LL+EFFORT exercise [difference of 0.23 (0.45) kg/cm2], and the CON condition. The change in lower body PPT was greater for LL+BFR exercise compared to LL exercise [difference of 0.40 (0.55) kg/cm2], LL+EFFORT exercise [difference of 0.36 (0.62) kg/cm2], and the CON condition. Ischaemic pain thresholds and tolerances did not change. Submaximal exercise with BFR resulted in systemic increases in PPT but had no influence on ischaemic pain sensitivity. This effect is likely unique to BFR as we did not see changes in the effort matched free flow condition.